2018
DOI: 10.1007/s12288-018-0959-4
|View full text |Cite
|
Sign up to set email alerts
|

Red Cell Transfusion Practices in Neonatal Intensive Care Unit: An Experience from Tertiary Care Centre

Abstract: Red cells are the most often transfused blood components during the neonatal period. The aim of the present study was to obtain information regarding the relationship of red cell transfusion with clinical outcomes and to evaluate red cell transfusion practices in neonatal centre of a tertiary care centre. The clinical history, blood component details and laboratory parameters were evaluated with clinical outcomes. The neonates requiring transfusion of red cells were then followed up in the Blood bank for vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…As compared to normal birth weight neonates, extremely low birth weight neonates required more frequent platelet transfusions when they were diagnosed with thrombocytopenia [ 14 ]. One cannot extrapolate adult transfusion data to fill gaps in neonatal transfusion cutoff [ 3 ]. Hemoglobin level in neonates differs from adults because they are age-dependent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As compared to normal birth weight neonates, extremely low birth weight neonates required more frequent platelet transfusions when they were diagnosed with thrombocytopenia [ 14 ]. One cannot extrapolate adult transfusion data to fill gaps in neonatal transfusion cutoff [ 3 ]. Hemoglobin level in neonates differs from adults because they are age-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…The blood volume in a full-term newborn is approximately 85 ml/kg while that in a preterm newborn is about 100 ml/kg and that in an adult is about 70 ml/kg. The miniature blood volume and rookie organ systems in the neonate call for novel proposals in neonatal blood transfusion practice [ 3 ]. The physiological puerility of different organ systems can put at peril those very low birth weight babies (VLBW) to metabolic imbalance following transfusion and their additives, and infectious and immunological hazards such as graft-versus-host disease (GVHD) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Greater than 80% of the participating blood centers in our study were part of a hospital/ hospital system. (Table 1) The data on transfusion practices in neonates and pediatrics is limited from India, as only a few academic care centers have published their experiences 4–7 . One of the reasons for such inappropriate data is due to highly variable transfusion practice both at the bedside (clinical use of blood) 8 as well as at the blood centers (blood banks) 9 .…”
Section: Introductionmentioning
confidence: 99%
“…(Table 1) The data on transfusion practices in neonates and pediatrics is limited from India, as only a few academic care centers have published their experiences. [4][5][6][7] One of the reasons for such inappropriate data is due to highly variable transfusion practice both at the bedside (clinical use of blood) 8 as well as at the blood centers (blood banks). 9 With recent advancements in transfusion medicine, aliquoting, component therapy, apheresis technology, and new available immune-hematological tests, the variation in blood center practices has widely increased.…”
Section: Introductionmentioning
confidence: 99%
“…After evaluating, retrospectively, the transfusion practices in critically ill neonates over 19 mo, the incidence of transfusion was 58.4%, PRBC being the most frequently transfused blood component. Several studies have found that the incidence of neonatal transfusion ranges from 20 to 90% [1,2].…”
mentioning
confidence: 99%